Day 1 Tue, November 17, 2020 2020
DOI: 10.2118/202460-ms
|View full text |Cite
|
Sign up to set email alerts
|

History Matching of Production Performance for Highly Faulted, Multi Layered, Clastic Oil Reservoirs using Artificial Intelligence and Data Analytics: A Novel Approach

Abstract: History Matching (HM) is one of the critical steps for dynamic reservoir modelling to establish a reliable predictive model. Numerous approaches have emerged over the decades to accomplish a robust history matched reservoir model ranging from the classical reservoir engineering approach to the widely accepted 3D numerical simulation approach and its variations. As geological complexity of the oil and gas field increases (multilayered reservoirs, heavily faulted) compounded with completion complexity (dual stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…The results showed that the ANN was expensive enough regarding the number of simulations that were required; however, good-quality results were achieved, in terms of uncertainty reduction, accuracy and speed. Mohmad et al [119] focused on the risk analysis area by developing a simple ANN to match a highly complex faulted reservoir with dual-string wells, creating a more efficient model that minimizes the risk uncertainty related to production and management plans. Their results showcased that this approach is much more competent, as far as the calculation time is concerned, when compared to conventional simulators.…”
Section: History Matching Based On Ann Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the ANN was expensive enough regarding the number of simulations that were required; however, good-quality results were achieved, in terms of uncertainty reduction, accuracy and speed. Mohmad et al [119] focused on the risk analysis area by developing a simple ANN to match a highly complex faulted reservoir with dual-string wells, creating a more efficient model that minimizes the risk uncertainty related to production and management plans. Their results showcased that this approach is much more competent, as far as the calculation time is concerned, when compared to conventional simulators.…”
Section: History Matching Based On Ann Modelsmentioning
confidence: 99%
“…ANNs with stochastic optimization [106,107] ANNs with dimensionality reduction methods [108] Ensembles of ANNs [109] RBFNNs, Generalized Regression ANNs, FSSC and ANFIS stochastic optimization [110][111][112] Direct history matching Supervised ANNs [114][115][116][117][118][119][120]126] Bayesian ML models [121,122,124,125] MARS, DTs, single-pass GRNNs [127] Unsupervised Self-Organizing Map (SOM) [131] Supervised SVR with dimensionality reduction and optimization [135] RNN [142,143] CNN [148,158] Unsupervised GAN [149,159] Piecewise Reconstruction from a Dictionary (PRaD) with pluri-PCA [151] Convolutional AutoEncoders [152,157] Reinforcement learning Reinforcement learning models [103,162] Currently, dozens of professional products used to set up ML models are available to developers, might that be related to research or commercial products. This palette includes client tools developed by major players in the market such as Google and Microsoft (Google cloud AI platform, Azure machine learning) as well as free tools such as TensorFlow by Google and the Anaconda distribution for Python.…”
Section: Indirect History Matching Supervisedmentioning
confidence: 99%